A “Late Antique” Mining Community in the North Kharga Oasis (Egypt) - Ikram, Salima.
The North Kharga Oasis Darb Ain Amur Survey (NKODAAS) has been exploring the extreme northern area and western extension of Kharga Oasis in order to locate and document hitherto undiscovered and unrecorded archaeological sites and material. The archaeological sites identified during the course of the survey are varied, including rock art, routes, mines, quarries, water dumps, wells, shelters, hamlets, and settlements. The site presented here is a Roman/“Late Antique” complex, including a church and several related areas of settlement and industrial activity devoted to alum mining and sandstone quarrying, that played a role in the history of the economy and landscape of Kharga Oasis.